Structure of bryophyte communities in the paramo complexes of Boyacá-Colombia - Moreno-Gaona, Diego A.; Morales-Puentes, María E.; Gil-Novoa, Jorge E.; Mercado-Gómez, Jorge D. (Revista de Biología Tropical, 2023)
Introduction: The Boyacá paramos cover 18.3 % of the Colombian surface, and are diverse in flora and fauna, moreover, have a high temperature, topography, and habitats, which allow these ecosystems to be centers of diversity in the Neotropics, and therefore they harbor a high diversity of bryophytes. Objectives: To analyze the structure and composition of the bryophyte communities of the paramos in the Boyacá complexes. Methods: Using literature, databases and herbariums records, the floristic composition, and the completeness of the sampling for the paramo and substrate complexes was evaluated. Results: We analyzed 5 132 specimens, with 343 species of mosses being the most diverse group, 256 liverworts and two hornworts. The sampling completeness analysis is 98 % representative. In addition, we found that the preference of substrates is terrestrial with 409 species and corticolous with 341. Alpha diversity of order 0D showed that Tota-Bijagual-Mamapacha (TBM) is the most diverse complex with 368 species, and Pisba (124) the least diverse; the 1D index showed that the complex (TBM) presented 178 species considered common, and the dominance of species (2D) was higher in the Iguaque-Merchán Complex with 119 dominant taxa and Guantiva-La Russia (105) and TBM (105) to a lesser number. 102). Conclusions: the analysis of beta diversity showed that 62 % of the dissimilarity in the composition of species between the complexes is due to the species turnover, the same happens with the divergence by substrates that is 51 %. Bryophytes in the Boyacá paramos represent 36.05 % of Colombian diversity, and 2.96 % worldwide.